Complete Genome Sequence of Mycoplasma ovipneumoniae Strain NM2010, Which Was Isolated from a Sheep in China - Xiao-hui WANG; Hai-bi HUANG; Chen CHENG; Ren-chao WANG; Jia-qi ZHENG; Yongqing HAO; Wen-guang ZHANG (Journal of Integrative Agriculture, 2014)
Mycoplasma ovipneumoniae, a kind of mycoplasma bacteria, commonly infects the respiratory tract causing respiratory disease in sheep and goats worldwide. Here, the complete genome sequence of M. ovipneumoniae strain NM2010 isolated from a sheep in China was reported for the first time.